CHANNEL MODELING OF THE OTH OPTICAL TRANSMISSION SYSTEM WITH QUADRATURE AMPLITUDE MODULATION - PEDYASH, Volodymyr (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The rapid development of services for providing broadband access to the Internet and multimedia content delivery services required the widespread use of fiber optic transmission systems (FOTS) for the transmission of digital traffic. The transmitter signal passes through an optical line, which includes optical fiber and optical amplifiers. In the optical fiber, linear and nonlinear distortions are introduced into the signal, and optical amplifiers generate additive noise of amplified spontaneous emission. In this paper, we develop a model of the optical channel of OTH system with QAM modulation, which takes into account linear and nonlinear distortions of the optical propagation medium and additive noise of the amplified spontaneous radiation of optical amplifiers. To obtain accurate results, the method of simulation modeling was used. The block diagram of the developed model contains a transmitter, an optical line and a coherent receiver of the optical signal. The expression for the time form of the electric field intensity of the optical signal at the transmitter output is given. Modeling of the optical fiber was performed by the split step Fourier method. The noise of the amplified spontaneous emission of optical amplifiers was formed in the frequency domain by means of the Fourier transform operation. The quality of the optical channel was estimated by calculating the average value of the Q-factor of the optical signal at the receiver output. The dependence of the Q-factor from the number of sections of the optical line and the power level of the optical signal was obtained. It is shown that to maximize the quality characteristics of the optical channel, the optimal value of the signal power should be used. The comparison of the obtained results with the data from specialized software products is carried out. Sufficient accuracy of the proposed model was demonstrated. It is recommended to use the developed channel model in the design of new and modernization of existing fragments of networks based on OTH systems with QAM modulation.